Towards a contextual approach to athletic performance enhancement: Reflections, perspectives, and applications - Zhang, C.-Q.; Baltzell, A. (Journal of Sport Psychology in Action, 2019)
Traditionally, mental training in sport and performance realms has mainly been based on the psychological skills training (PST) procedures which include assumptions of changing, replacing, and eliminating negative thoughts for performance enhancement (Gardner & Moore, 2004). The contextual approach of changing the relationship with self and context was not part of the theory-to-practice paradigm. With the pioneering publication of the intervention protocol of the Mindfulness-Acceptance-Commitment approach in sport (MAC; Gardner & Moore, 2007), mindfulness, and acceptance approaches started to become adopted by researchers and practitioners in sport context, which also include the self-compassion training for athletes (e.g., Mosewich, Crocker, Kowalski, & DeLongis, 2013). Several mindfulness and acceptance based intervention programs were developed such as the Mindful Sport Performance Enhancement (MSPE; Kaufman, Glass, & Pineau, 2018) and the Mindfulness Meditation Training for Sport (MMTS; Baltzell & Summers, 2018). Empirical evidence on the effectiveness of the interventions has been preliminarily established including increased mindfulness, flow, and performance, and decreased competitive anxiety (Noetel, Ciarrochi, Van Zanden, & Lonsdale, 2017). To inform future research and applied practice, it is time to take stock of what we have accomplished during the past 15 years in terms of reflections, perspectives, and applications of the contextual approach to athletic performance enhancement. The current special issue of the Journal of Sport Psychology in Action, which includes eight papers, indeed serves this purpose.